613.DEVELOPMENT OF THE ENERGY MANAGEMENT INFORMATIVE SYSTEM - Katerina, Dimovski; Gligorce, Vrtanoski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2020)
The Industrial Revolution initiates an era of mass production and industrialization of cities that provides all the comforts of modern living, and thus the unconscious pollution of the planet, climate change and global warming. According to the Goddard Institute of Space Studies (GISS) of the National Aeronautics and Space Agency, the depths in the ozone layer and the increased carbon dioxide emissions in the air are responsible for increasing the surface temperature of the Earth by 1 °C in the last 100 years. As temperature rises on the Earth, we face an increase of sea level levels, a change in precipitation on a regional scale, frequent extremes in temperatures like heat waves, droughts, floods and snowstorms. The warming is felt more on the land surface than in the sea waters, while the most significant is the Arctic, where glaciers are starting to disintegrate, and this can lead to the eradication of some species of flora and fauna. For the human, global warming will lead to the challenge of providing food and leaving populated areas close to flooded areas. Many countries support the climate change onvention and contribute to reducing the impact of GTC with climate engineering, with global warming being stopped before reaching 2 °C compared to the period before industrialization. By implementing a system for managing energy and renewable energy sources, it will contribute to the rational utilization of energy and energy sources and the formation of a sustainable society that will affect in future reduction of carbon dioxide emissions in the atmosphere.